2015
DOI: 10.1371/journal.pone.0141093
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in Relation to Coronary Atherosclerotic Plaque Burden, Volume and Composition on Intravascular Ultrasound

Abstract: BackgroundThis study aimed to evaluate the relationship between cigarette smoking and coronary atherosclerotic burden, volume and composition as determined in-vivo by grayscale and virtual histology (VH) intravascular ultrasound (IVUS).Methods and ResultsBetween 2008 and 2011, (VH-)IVUS of a non-culprit coronary artery was performed in 581 patients undergoing coronary angiography. To account for differences in baseline characteristics, current smokers were matched to never smokers by age, gender and indication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
9
1
Order By: Relevance
“…In the whole plaque, the difference of plaque components between the two groups was not significant (c). The mean plaque volume in the later CAD group was greater than that in the premature CAD group, and every component was greater too (d) smoked, or quit more than 1 year ago [37,38]. After MI, continued smokers with a relative risk of 1.51 (95% CI 1.10-2.07) recurrent coronary events compared with nonsmokers, while the risk declined to equal that of nonsmokers 3 years after cessation [39].…”
Section: Discussionmentioning
confidence: 95%
“…In the whole plaque, the difference of plaque components between the two groups was not significant (c). The mean plaque volume in the later CAD group was greater than that in the premature CAD group, and every component was greater too (d) smoked, or quit more than 1 year ago [37,38]. After MI, continued smokers with a relative risk of 1.51 (95% CI 1.10-2.07) recurrent coronary events compared with nonsmokers, while the risk declined to equal that of nonsmokers 3 years after cessation [39].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have demonstrated that smoking is the most important risk factor associated with the severity of coronary artery disease and is significantly linked with increased risk of coronary plaque vulnerability, myocardial infarction, and cardiovascular death [ 29 , 30 ]. Previous report showed that the prevalence of smoking in younger coronary artery disease individuals (<45 years of age) ranged from 60% to 90% as compared to 24% to 56% in subjects aged 45 years and over [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was both a risk factor for CAD, and a strong predictor of CAD mortality, although the risk decreased with smoking cessation 11 . Additionally, previous studies have showed that smoking is the most common risk factor associated with the complexity and severity of coronary artery disease and is significantly associated with increased risk of coronary plaque rupture, myocardial infarction, and increased cardiovascular morbidity and mortality [12][13][14] . Kannel et al 15 found in patients included in the Framingham Heart Study that smoking was associated with a three-fold increase in the relative risk for CAD in smokers age 35 to 44, compared to nonsmokers.…”
Section: Discussionmentioning
confidence: 99%